TEACHER APPROACH IN INCULCATING DISCIPLINE ATTITUDES IN THE FOURTH GRADE STUDENTS AT SDN PATOKAN 2 DISTRICT TAHUN 2017 - Dodik Eko Yulianto (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Abdurachman Saleh Situbondo, 2017)
This study aims to determine the approach of teachers using behavior modification and in planting student discipline attitude. the title proposed in this study is